The role of sentinel lymph node status performed in melanoma patients with local recurrence or in transit metastasis. Issue 5 (May 2021) - Mattavelli, Ilaria; Maurichi, Andrea; Galeone, Carlotta; Gallino, Gianfranco; Barbieri, Consuelo; Leva, Andrea; Tolomio, Elena; Valeri, Barbara; Cossa, Mara; Patuzzo, Roberto; Santinami, Mario
Abstract: Background: Sentinel Node Biopsy (SNB) is routinely performed for primary melanoma, but its role in the treatment of Local Recurrence (LR) and In-Transit metastasis (IT) is controversial. This study aims to assess the role of SNB in melanoma patients who developed first loco-regional recurrence. Methods: A series of consecutive melanoma patients who received SNB for a first IT or LR at the National Cancer Institute of Milan, Italy, from 2000 to 2015 were selected from a prospective database. Clinicopathological characteristics were analyzed. Results: Seventy-two patients met selection criteria. Forty-three patients (59.7%) received SNB for LR and 29 (40.3%) for IT. The average interval between treatment of primitive melanoma and first recurrence diagnosis was 19 months (interquartile range: 6.9–49.0). SN identification rate was 97.2%. SN positivity was detected in 26 (37.1%) patients. The SN-positive ratein melanoma patients who had LR or IT was significantly higher than reported for primary tumours. Of patients with nodal involvement 17 had LR and 9 IT lesions. Disease Free Survival (DFS) was slightly higher in SN negative patients, in the absence of statistically significant differences. Overall Survival (OS) analysis showed similar values in the two groups. Conclusion: Since DFS and OS do not show significant differences between SN negative and positive patients, our data do not give clear indications about performing SNB in case of first LR or IT. However, we suggest submitting patients with LR to this procedure to obtain a more accurate staging and eventually candidate these patients to adjuvant treatment.